MORPHOMETRIC CHANGES AND POST-PLANTING GROWTH AS A RESPONSE TO HARDENING ON Tabebuia roseo-alba SEEDLINGS - Cadorin, Danielle ACCO; Malavasi, Ubirajara Contro; Malavasi, Marlene de Matos; Dranski, João Alexandre Lopes; Coutinho, Pablo Wenderson Ribeiro (Floresta, 2021)
The essay evaluated morphometric changes in response to stem bending and jasmonic acid on Tabebuia roseo-alba (Ridl). Sand. seedlings. We tested 20 daily stem bendings and applications of 1 μmol L-1 of jasmonic acid for 4 or 8 weeks. Stem bending for 8 weeks resulted in seedlings with fewer leaves and smaller shoot dry biomass compared to seedlings subjected to the other treatments. The results of electrolyte leakage from root tissues of control seedlings showed higher value compared to results from seedlings subjected to the test treatments. After planting, we did not detect differences in height and diameter increments from seedlings subjected to the test treatments. Therefore, hardening methods did not improve post-planting seedling growth.